2019
DOI: 10.3390/ijerph16040614
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Environmental Conditions on Marathon Running Performance in Men Competing in Boston Marathon from 1897 to 2018

Abstract: This study investigated the effects of weather conditions on male performance during the Boston Marathon from 1897 to 2018. A total of 383,982 observations from 244,642 different finishers were analysed using Generalized Additive Mixed Models. All runners, annual top 100 finishers and annual top ten finishers were considered. Weather conditions, on race day, were: average air temperature (°C), precipitations (mm), wet-bulb globe temperature (WBGT) (°C), wind speed (km/h), wind direction (N, S, W, E) and pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
0
31
3
Order By: Relevance
“…Moreover, the role of environmental conditions was not considered, since detailed data on temperature, humidity, and wind were not available, and these environmental parameters might influence endurance performance [34]. For instance, it has been observed recently that an increase in temperature by 1 °C was related to a slower race time by ~2 min in the Boston marathon [35]. To study the effect of environmental conditions in the Ljubljana half-marathon and marathon in the future, it would be necessary to consider a large number of calendar years following the paradigm of the Boston marathon [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the role of environmental conditions was not considered, since detailed data on temperature, humidity, and wind were not available, and these environmental parameters might influence endurance performance [34]. For instance, it has been observed recently that an increase in temperature by 1 °C was related to a slower race time by ~2 min in the Boston marathon [35]. To study the effect of environmental conditions in the Ljubljana half-marathon and marathon in the future, it would be necessary to consider a large number of calendar years following the paradigm of the Boston marathon [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been observed recently that an increase in temperature by 1 °C was related to a slower race time by ~2 min in the Boston marathon [35]. To study the effect of environmental conditions in the Ljubljana half-marathon and marathon in the future, it would be necessary to consider a large number of calendar years following the paradigm of the Boston marathon [34,35]. On the other hand, a strength of the study was its novelty, since it was the first to examine performance and pacing in age groups of half-marathon runners.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research has found that marathon events are mostly distributed in spring (week 14 to 17) and autumn (week 41 to 44) and the average temperature of host cities varies close to optimal value for long distance races [17]. Some studies have analyzed the changing trend of meteorological values of marathon such as temperature, humidity, air quality, and wind speed over time, and found that the climate has an impact on participants' physical sensations and performance in the race [11,13,[18][19][20]. There is also a large body of literature investigating the impact of different climates on the physical conditions of marathon runners.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, it has been demonstrated that the evaluation of fractional exhaled nitric oxide (FeNO), a remarkable biomarker presenting increased levels in association with pulmonary inflammation, can be useful for monitoring pulmonary inflammatory status in different situations [54][55][56], including in the context of running [46,57]. Other points that deserve to be mentioned are related to the inclusion of only men in this study, the age of the participants, and also, to the environmental conditions present during the marathon event [58]. With regard to the inclusion of only men, although the literature shows that the participation of women in marathons has increased, leading to a decrease in the proportion of men to women, the number of men participating in these races is still greater than that of women.…”
Section: Discussionmentioning
confidence: 91%